Freedom of religion and non-discrimination based on gender identity and sexual orientation in Ukraine: corporate policy commitments in situations of conflicting social expectations - Horbachevska, Tamara (Human rights review, 2024)
Conflicting social expectations in a particular state affect the interpretation and implementation of international human rights law. Ideological, religious, and legal factors related to the protection of freedom of religion or belief (FoRB) and freedom from discrimination based on sexual orientation and gender identity (SOGI) in Ukraine put businesses under social pressure. Businesses thus face a legitimate dilemma whether to follow national social expectations perceiving FoRB and freedom from discrimination based on SOGI as rights in conflict or expectations arising from international human rights law establishing both freedoms as equal and non-clashing. Based on desk research and in-depth interviews with business policymakers the article identifies neutrality, ignoring, and active engagement strategies when providing corporate respect to FoRB and SOGI under the business and human rights framework ‘Protect, Respect, Remedy’ which requires responsible business conduct. The article concludes with the implications each strategy has for resolving presumed clashes between FoRB and SOGI at the community level.